(untitled) (Research, Society and Development, 2022)
The current models of agriculture and development in general are proving to be unsustainable, given their bases in exacerbated waste, exhaustion of natural resources, incorrect disposal of waste that cause serious damage to the environment. Because of this, a change in society’s mentality is necessary, shifting from the irresponsible development aimed only at profit, to an attitude of caution with natural resources and detachment from unbridled profit, through environmental sustainability, that is, the perception that man belongs to the environment, not the opposite. Thus, the objective of this paper is to discuss and present the introductory concepts of organic production and the organic market from the local and international perspective. The construction of the article went through secondary data and used renowned authors for the discussions from 4 topics. Being, The concept of organic agriculture; History of agriculture and organic agriculture under the agroecology view; Profile of organic consumers in Brazil; National rules and regulations. It was concluded that Brazil is not among the first 10 countries with the largest organic production area in South America, even though the demand for ecologically friendly products has increased. To this end, it is understood that there is still a long way to go, especially in raising the population’s awareness, with a view to improving food safety in general, since nutrition is interconnected with health as the main reason for the acquisition of organic products.